Analysis Of Effect Of Service Quality, Quality Products, And Prices On Customer Satisfaction (Case Study At PT Asuransi Tri Pakarta Customer Branch Semarang) - Widowati, Sri Yuni (Economics and Business Solutions Journal, 2017)
The purpose of the study was to analysis: (1) the impact of service quality on customer satisfaction on PT Asuransi Tri Pakarta Semarang, (2) inflence of product quality for customer satisfaction on PT Asuransi Tri Pakarta Semarang, (3) the effect of price on customer satisfaction on PT Asuransi Tri Pakarta Semarang.The population of this study were customers of 75 employees on PT Asuransi Tri Pakarta Semarang.  This study was a population.  The Data of this study was collected by using questionnaire.  Data analysis was conducted by  multiple regression analysis.The result shows that (1) there is influence service quality, product quality and price on customer satisfaction on PT Asuransi Tri Pakarta Semarang.